The effect of the rs1799931 G857A (G286E) polymorphism on N-acetyltransferase 2-mediated carcinogen metabolism and genotoxicity differs with heterocyclic amine exposure - Hein, David W.; Salazar-González, Raúl A.; Doll, Mark A.; Zang, Yu (Archives of toxicology, 2023)
Human N -acetyltransferase 2 (NAT2) is subject to genetic polymorphism in human populations. In addition to the reference NAT2*4 allele, two genetic variant alleles ( NAT2*5B and NAT2*7B ) are common in Europe and Asia, respectively. NAT2*5B possesses a signature rs1801280 T341C (I114T) single-nucleotide polymorphism (SNP), whereas NAT2*7B possesses a signature rs1799931 G857A (G286E) SNP. NAT2 alleles possessing the T341C (I114T) or G857A (G286E) SNP were recombinant expressed in yeast and tested for capacity to catalyze the O -acetylation of the N -hydroxy metabolites of heterocyclic amines (HCAs). The T341C (I114T) SNP reduced the O -acetylation of N -hydroxy-2-amino-3-methylimidazo [4,5-f] quinoline ( N- OH-IQ), N -hydroxy-2-amino-3,8-dimethylimidazo [4,5-f] quinoxaline ( N- OH-MeIQx) and N -hydroxy- 2-amino-1-methyl-6-phenylimidazo[4,5-b] pyridine ( N- OH-PhIP), whereas the G857A (G286E) SNP reduced the O -acetylation of N- OH-IQ and N- OH-MeIQx but not N- OH-PhIP. The G857A (G286E) SNP significantly ( p < 0.05) reduced apparent K m toward N- OH-PhIP but did not significantly ( p > 0.05) affect apparent V max . Cultures of DNA repair-deficient Chinese hamster ovary (CHO) cells transfected with human CYP1A2 and NAT2*4, NAT2*5B or NAT2*7B alleles were incubated with various concentrations of IQ, MeIQx or PhIP and double-stranded DNA damage and reactive oxygen species (ROS) were measured. Transfection with human CYP1A2 did not significantly ( p > 0.05) increase HCA-induced DNA damage and ROS over un-transfected cells. Additional transfection with NAT2*4 , NAT2*5B or NAT2*7B allele increased both DNA damage and ROS. The magnitude of the increases was both NAT2 allele- and substrate-dependent showing the same pattern as observed for the O -acetylation of the N -hydroxylated HCAs suggesting that both are mediated via NAT2-catalyzed O -acetylation. The results document the role of NAT2 and its genetic polymorphism on the O -acetylation and genotoxicity of HCAs.